Analyzing the Theta state of brainwave signal after HR intervention using EEG / Muhammad Fariz Samsul - Samsul, Muhammad Fariz (2008)
This research analyzing the Theta state of brainwave using EEG and Horizontal Rotation (HR). EEG signals were captured from 32 students for 3 sessions, beginning, middle and end of semester before and after they underwent HR using two-channel bipolar connection in a controlled environment. The signals were filtered and classified into four main frequency bands: Delta, Theta, Alpha and Beta. The Theta states of brainwave were taken out for analyses. Graphs were plotted and paired T-test analysis was used to show the correlation between the left and right brainwave before and after HR to verify the brainwave synchronization. Another test was done to show the student's brainwave behavior for 3 sessions, beginning, middle and end of semester. It was observed that after HR, brainwaves were more balanced for all three sessions. In conclusion, there was proven that HR could synchronize brainwave.